2023
DOI: 10.1002/jgc4.1694
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal patient perceptions of receiving difficult news over the telephone

Abstract: Difficult news has been described as any news that adversely and seriously affects an individual's view of their future. Research in oncology genetic counseling demonstrated that individuals do not prefer in‐person or telephone delivery of their genetic test results. However, in the prenatal setting, there is limited research examining how patients prefer news related to their pregnancies be disclosed. This study aimed to assess the experiences and preferences of prenatal patients who received difficult news b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Use of telemedicine has increased over the past few years following the COVID-19 pandemic [73]. Two studies provide guidance for HCPs conducting video consultations in prenatal setting [74,75 ▪▪ ]. An American study published in 2013 suggests that prepating patients with detailed information on what to expect from their virtual consultation ahead of the appointment may improve their experience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of telemedicine has increased over the past few years following the COVID-19 pandemic [73]. Two studies provide guidance for HCPs conducting video consultations in prenatal setting [74,75 ▪▪ ]. An American study published in 2013 suggests that prepating patients with detailed information on what to expect from their virtual consultation ahead of the appointment may improve their experience.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study that interviewed 16 women who had received unexpected news by telephone has concluded that a patient-centred approach is most effective and beneficial for delivering difficult news to prenatal patients [75 ▪▪ ]. Signposting to written information, support group resources and follow-up care is deemed essential also in this setting [75 ▪▪ ]. Finally, feedback should be sought from the patients in order to improve this new type of service [74].…”
Section: Resultsmentioning
confidence: 99%
“…Patients' preference on the route of receiving difficult news varies based on the patient's understanding, support system, and personal values. 42 While further research is needed, shared decision-making continues to be central to patient care regardless of visit type. 42 Overall, telehealth is highly accepted but there continue to be limitations, such as, lack of appropriate funding for implementation, equipment, support services, and in the US insurance coverage and reimbursement barriers.…”
Section: Acceptability Of Telehealth Servicesmentioning
confidence: 99%
“…42 While further research is needed, shared decision-making continues to be central to patient care regardless of visit type. 42 Overall, telehealth is highly accepted but there continue to be limitations, such as, lack of appropriate funding for implementation, equipment, support services, and in the US insurance coverage and reimbursement barriers. 43 However, even in light of these barriers, a review of the literature indicates that the benefits far outweigh the limitations.…”
Section: Acceptability Of Telehealth Servicesmentioning
confidence: 99%
See 1 more Smart Citation